Relationship between social capital indicators and lifestyle in Brazilian adults - Mathias Roberto Loch; Regina Kazue Tanno de Souza; Arthur Eumann Mesas; David Martinez-Gómez; Fernando Rodríguez-Artalejo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
The present study examined the relationship between indicators of social capital and health-related behaviors. A cross-sectional study was conducted on a sample of 1,062 participants representative of the population aged 40 years or older from a city in Southern Brazil. The following indicators of social capital were examined: number of friends, number of people they could borrow money from when in need; extent of trust in community members; number of times members of the community help each other; community safety; and extent of membership in community activities. Also, an overall score of social capital including all indicators was calculated. A poor social capital was associated with insufficient leisure-time physical activity (OR = 1.70; 95%CI: 1.07-2.70), low consumption of fruits and vegetables (OR = 1.53; 95%CI: 1.05-2.24), and smoking (OR = 1.97; 95%CI: 1.21-3.21). No clear association was found between capital social and binge drinking. A score of social capital showed an inverse relationship with the number of prevalent risk behaviors (p < 0.001). These results reinforce that policies to promote health should consider social capital.